1976
DOI: 10.1111/j.1432-1033.1976.tb10867.x
|View full text |Cite
|
Sign up to set email alerts
|

Protease I from Escherichia coli

Abstract: Protease I, a periplasmic endopeptidase from Escherichia coli has been further purified by a modified procedure. While the purified protein consists of a single polypeptide chain of about 21 000 daltons, its molecular weight in dilute salt solution was estimated to be near 43000, suggesting that the enzyme has a marked tendency to dimerize. It has only one disulphide bond and is very sensitive to urea.In agreement with previous evidence of a chymotrypsin-like specificity, hydrolytic assays of various p-nitroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 35 publications
(9 reference statements)
0
16
0
Order By: Relevance
“…Although our detecting method is not definitive, it is likely that this dust proteinase is aspergillopepsin I (aspergillopeptidase A; extracellular acid protease; proteinase B), which has been variously reported to exist as ∼22 and ∼43 kDa proteins. 28,31,32 Microbial proteinases are known to multimerize in solution and it is likely that our ∼86 kDa product represents a tetramer of aspergillopepsin I 33 (Figure 1; and P Kolattukudy personal communication). Aspergillopepsins are secreted by many aspergillus species and we have used the highly allergenic A. oryzae aspergillopepsin for many years to generate allergic lung disease in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although our detecting method is not definitive, it is likely that this dust proteinase is aspergillopepsin I (aspergillopeptidase A; extracellular acid protease; proteinase B), which has been variously reported to exist as ∼22 and ∼43 kDa proteins. 28,31,32 Microbial proteinases are known to multimerize in solution and it is likely that our ∼86 kDa product represents a tetramer of aspergillopepsin I 33 (Figure 1; and P Kolattukudy personal communication). Aspergillopepsins are secreted by many aspergillus species and we have used the highly allergenic A. oryzae aspergillopepsin for many years to generate allergic lung disease in mice.…”
Section: Discussionmentioning
confidence: 99%
“…One apparent hazard with such analyses is that enzymological methods may give unspecific reactions caused by bacterial enzymes with tryptic or chymotryptic activity. It has been postulated that intestinal bacteria possessed no such activity (1 3, 19), but proteases with tryptic and chymotryptic activity were recently isolated from E. coli (29,30).…”
mentioning
confidence: 99%
“…Only the activity which was tightly bound to gramicidin S-Sepharose 4B was studied further. Pacaud et al (1976) found that E. coli contained protease I, an enzyme capable of cleavingp-nitrophenyl esters of N-substituted amino acids and possessing a 'chymotrypsinlike' substrate specificity. It may well be that this enzyme could cleave Z-L-Ala-L-Ala-L-LeupNA and possibly the activity towards this substrate that did not bind to gramicidin SSepharose 4B was protease I.…”
Section: Resultsmentioning
confidence: 99%
“…The scarcity of biochemical data on the purified E. coli enzymes is caused by difficulties in their isolation, the extremely low concentration within the cells an'd the absence of specific affinity adsorbents suitable for the simultaneous isolation of several proteases. ' Chymotrypsin-like' protease I (Pacaud & Uriel, 1971 ;Pacaud et al, 1976) and 'trypsin-like' protease I1 (Pacaud & Richaud, 1975;Pacaud, 1976) are the only endopeptidases of E. coli to have been purified and studied in some detail.…”
Section: Introductionmentioning
confidence: 99%